Solving Preventive-Corrective SCOPF by a Hybrid Computational Strategy - Xu, Yan; Dong, Zhao Yang; Zhang, Rui; Wong, Kit Po; Lai, Mingyong (IEEE transactions on power systems, 2014)
Preventive control (PC) and corrective control (CC) are complementary actions in protecting large power systems against the risk of blackout. This paper addresses the optimal coordination between PC and CC via a preventive-corrective security-constrained optimal power flow model. The objective is to minimize the total expected-security-control cost which is the sum of the costs of PC and CC considering the probability of the contingencies. The constraints include system operating limits in pre- and post-contingency states, the existence of the post-contingency short-term equilibrium, and the coupling constraints on the CC actions. To solve the model, a hybrid computational strategy combining evolutionary algorithm and interior-point method is developed. The solution process consists of globally searching the critical feasible region and locally optimizing the operating variables in the found region, the two procedures interact iteratively to progressively tighten the solution region leading to the final solution. The proposed model and computational strategy are demonstrated on the IEEE 14-bus and 118-bus test systems. To speed up the computation, parallel processing of the approach is implemented.